2018
DOI: 10.2196/10482
|View full text |Cite
|
Sign up to set email alerts
|

A Smartphone Game-Based Intervention (Tumaini) to Prevent HIV Among Young Africans: Pilot Randomized Controlled Trial

Abstract: BackgroundThere is a pressing need to ensure that youth in high HIV prevalence settings are prepared for a safer sexual debut. Smartphone ownership is increasing dramatically in low-income and middle-income countries. Smartphone games that are appropriately grounded in behavioral theory and evidence-based practice have the potential to become valuable tools in youth HIV prevention efforts in Sub-Saharan Africa.ObjectiveTo pilot-test a theory-based, empirically grounded smartphone game for young Kenyans designe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
116
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(118 citation statements)
references
References 47 publications
1
116
0
1
Order By: Relevance
“…Additional results related to acceptability and to the study’s secondary (behavioral) outcomes were analyzed, and these are reported in separate [27] and forthcoming publications.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additional results related to acceptability and to the study’s secondary (behavioral) outcomes were analyzed, and these are reported in separate [27] and forthcoming publications.…”
Section: Resultsmentioning
confidence: 99%
“…Primary outcomes for this study focused on the feasibility and safety of the study. Secondary outcomes included acceptability of the game and behavioral mediators of sexual initiation and condom use, reported elsewhere [27].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(41) In HIV, telehealth studies have increased HIV risks awareness and retention into care. (42,43) Telehealth innovations targeting communicable diseases and maternal-child health have been found to be highly acceptable, feasible, and have significantly improved medication adherence, engagement in care, and use of health services. (40) Therefore, it is important to use the already established precedence in these disease areas to increase the use of telehealth along the HCC.…”
Section: Discussionmentioning
confidence: 99%
“…App entertainment and gamification have been found to improve user engagement and the reach of sexual health app interventions. 37,40 The PrEP-related apps did not score well in terms of engagement, thus apps for improving PrEP utilisation may benefit from incorporating additional gaming and entertainment features. PrEP-related apps could also benefit from including more features that allow for app user communication with healthcare providers or educators, 36,39 tracking of key personal sexual behaviours 37,41 and locating other types of sexual healthcare services, such as HIV testing.…”
Section: Key Findingsmentioning
confidence: 99%